Longitudinal links between maternal directives, children’s engagement in family conversations, and child linguistic skills - Tulviste, Tiia; Tamm, Anni (Frontiers in Psychology, 2023)
Background Research on mother–child verbal interaction is largely inspired by Vygotsky. The results align with his view that children acquire language and culture-specific ways of using language through actively participating in daily conversations with adults. Supporting Vygotsky’s concept of the Zone of Proximal Development, the facilitative features of such conversations have been found to depend on age, the level of the child’s language skills, and the interactional context. Most previous studies in the field have been conducted in English-speaking Western families with a focus on the first years of children’s lives. As Estonian middle-class mothers have been found to put greater emphasis on controlling children than mothers from other cultural contexts, we included the frequency of using directives as one of the features of mothers’ speech that might have an impact on child language development. Aim Accordingly, the current study explored the relative impact of various aspects of mother–child interaction (e.g., mothers’ vocabulary diversity, use of attentional and behavioral directives, wh-questions, and the amount of children’s talk) on children’s language skills using data collected from Estonian middle-class families at two timepoints, 1 year apart. As a novel approach to this topic, the study also examined the correlation between mothers’ input features and children’s participation in the parent–child conversation. Method A total of 87 children aged 3;0 and 4;0 and their mothers participated in the study. We observed the mother–child interactions during a semistructured videotaped game played at home. Mothers reported their children’s language skills via the ECDI-III. Children’s language comprehension and production were measured using the examiner-administered NRDLS. Results and conclusion Although the results showed somewhat differential effects of various aspects of mothers’ speech on different measures of child language skills at two timepoints, the diversity of mothers’ speech was positively, and mothers’ frequent use of directives negatively related to children’s language skills. At both ages, the diversity of mothers’ speech predicted the amount of children’s verbal contribution to conversations. The findings will be discussed in light of Vygotskian and his followers’ theoretical views and theories about child language development.